Parasitoid communities attacking externally feeding folivorous Lepidoptera in New Guinea rainforest - Hrček, Jan (Jihočeská univerzita, 2008)
The host - parasitoid community of externally feeding folivorous Lepidoptera and their parasitoids was studied on 45 focal tree species in a New Guinea rainforest. The patterns of parasitation rate, parasitoid species richness and parasitoid host specificity are described.
Parasitoid communities attacking externally feeding folivorous Lepidoptera in New Guinea rainforest